MANAJEMEN PENINGKATAN MUTU PENDIDIKAN MENUJU ERA SOCIETY 5.0 - Mahidin Mahidin (JGK (Jurnal Guru Kita), 2023)
Management of Educational Quality Improvement Towards the Era of Society 5.0. The nation's generation will face the era of society 5.0 which integrates artificial intelligence or digital technology in various life activities. Various hopes and challenges have become a reality that must be faced by every generation. In facing this reality, there is no other way but to prepare the generation as well as possible according to the developments and needs of the times. Quality education is one of the strategic efforts that can be made to prepare a generation that is ready to contribute and collaborate according to the times. This research was conducted to describe the management of improving the quality of education towards the era of society 5.0. The research was conducted using a qualitative paradigm with a literature study process. Where researchers perform data analysis by accessing data or references, organizing, sorting, categorizing, classifying. Then the data is presented through a simpler, logical, and systematic narrative. The results of the analysis can be described that quality education can be realized if educational institutions have good leadership, accurate analysis and information, measurable strategic quality planning, structured human resource development, adaptive process quality management, quality results that have outputs and outcomes , as well as customer or wider community satisfaction with the processes and results of these educational institutions.